Spatial Pattern of Water Quality on Coral Reef Area Around Kaledupa Island - Hadiwijaya L. Salim; Dini Purbani; Agustin Rustam; Yulius -; Devi D. Suryono; Joko Prihantono (Pusat Riset Kelautan, 2016)
Healthy coral reefs depends on the quality of the waters , so that research and monitoring of water quality becomes important. This research attempt to asses marine waters quality at kaledupa island and it’ s surrounding waters on October and November 2014. 33 In-situ samples were collected using multiparameters tool purposively which are categorized into physical parameters (temperature, turbidity and clarity), and chemical parameters (DO, salinity and pH). Waters quality defined by STORET method based on Ministry of Living Environment decree number 115 year of 2003. Analysis geographically has been conducted to describe distribution of waters quality spatially. The result shows that Kaledupa waters has sustain slightly pollution, especially on DO, turbidity, temperature and salinity parameters which have deviated from standard values. The light pollution in Kaledupa waters is suspected caused by the entry of abundance organic matter and shallow bathymetry.